Diversity and population structure of common bean from Brazil - Blair, Matthew W.; Brondani, Rosana Pereira V.; Díaz, Lucy M.; Peloso, Maria José del (Wiley, 2013)
Brazil is arguably the world's largest bean producing country and the crop is an important cultural and nutritional component of food in this part of South America. Common bean (Phaseolus vulgaris L.) is cultivated in almost all Brazilian states by small and large producers in diverse production systems and holds great economic and social standing. The goal of this study was to evaluate a collection of 362 common bean landraces and cultivars from Brazil to determine the genetic diversity found in different regions of the country. We performed principal component and population structure analyses so as to understand the subgroups and races found in Brazil. The optimum number of subgroups in the Brazilian germplasm was found to be K = 5 and at this level, the Mesoamerican genepool was subdivided into four subgroups, which remained separate from the Andean subgroup (A1). The M2 and M3 subgroups presented high diversity and high levels of allele mixing between genepools. Subgroup and genepool identities were confirmed by morphological traits such as seed size and phaseolin protein types. Allele switching between the genepools was common for growth habits and phaseolin. The association of the subgroups with commercial classes of Brazilian beans (Carioca, Preto, Rosinha, and Roxinho Mesoamerican types or Jalo and Roxo Andean types) is discussed as is the potential for specific subraces among the germplasm in Brazil.